Storage effect on quality attributes of combine mild heat and ultraviolet irradiated roselle (Hibiscus sabdariffa) juice compare with thermal treatment - Kamarul Zaman, Amanina Amani; Shamsudin, Rosnah; Mohd Adzahan, Noranizan (Faculty of Food Science and Nutrition, Universiti Malaysia Sabah, 2017)
Roselle juice is high in vitamin C and anthocyanin contents. Commercial thermal pasteurization affect the quality of roselle juice especially the anthocyanin color pigment and heat sensitive vitamin C. Extraction with mild heating able to extract more yields with clear juice to meet limitation of UV-C. Combine mild heat extraction (60 °C, 30 minutes) and UV-C treatment (65.86mJ/cm²) show significantly no difference in anthocyanin after treatment. Color of roselle juice more acceptable in appearance compare with thermally pasteurized roselle juice. Other properties of physicochemical (pH, titratable acidity, total soluble solid and turbidity) also shows promising result for combine mild heat and UVC treatment. Ascorbic acid of roselle juice remains higher compare to thermally pasteurized (90°C for 2 minutes) roselle juice. Microbiologically, the combine treatment managed to extend the shelf life of roselle juice for 6 weeks of storage at 4±2°C for 8 weeks.